Comparison of fine-needle aspiration and fine-needle biopsy devices for endoscopic ultrasound-guided sampling of solid lesions: a systemic review and meta-analysis - van Riet, Priscilla A.; Erler, Nicole S.; Bruno, Marco J.; Cahen, Djuna L. (Endoscopy, 2020)
Background Endoscopic ultrasound (EUS)-guided tissue acquisition is extensively used, but the optimal sampling device is still a matter of debate. We performed meta-analyses on studies comparing fine-needle aspiration (FNA) with fine-needle biopsy (FNB) needles, and studies comparing different FNB needles.Methods Online databases were searched for randomized controlled trials (RCTs) of at least 50 cases with a suspected solid pancreatic or nonpancreatic lesion that compared FNA with FNB needles. Outcome measures included diagnostic accuracy, adequacy, number of passes, presence of tissue cores, and adverse events. We also performed meta-regression analysis on the effect of FNB design on diagnostic accuracy. Quality was assessed using the QUADAS-2 tool.Results 18 RCTs comparing FNA with FNB needles were included. FNB provided a higher pooled diagnostic accuracy (87 % vs. 80 %; P = 0.02) and tissue core rate (80 % vs. 62 %; P = 0.002), and allowed diagnosis with fewer passes (P = 0.03), in both pancreatic and nonpancreatic lesions. A total of 93 studies were included comparing different FNB devices. Pooled diagnostic accuracy was higher for forward-facing bevel needles than for the reverse bevel needle. In this analysis, study quality was low and heterogeneity was high (I2 = 80 %).Conclusion FNB outperformed FNA when sampling pancreatic and nonpancreatic lesions. Forward-facing bevel FNB needles seemed to outperform the reverse bevel FNB needle, but the low quality of evidence prevents us from making strong recommendations on the optimal FNB design.